2015
DOI: 10.1016/j.jtcvs.2015.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biological significance of stem-like CD133+CXCR4+ cells in esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma cells coexpressing CD133 and CXCR4 possess the characteristics of cancer stem cells. The concomitant high CD133-CXCR4 expression might be a novel marker for predicting the poor prognosis of patients with esophageal squamous cell carcinoma, and CD133 and CXCR4 may serve as potential therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
(40 reference statements)
3
28
0
Order By: Relevance
“…Then, EIF3B antibody (Abcam, Cambridge, UK) was used to detect the expression of the related protein. Based on the measurement standard described previously [22], all cases were separated into two groups: a low expression level group for scores 0 and 1, and a high expression level group for scores 2 and 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, EIF3B antibody (Abcam, Cambridge, UK) was used to detect the expression of the related protein. Based on the measurement standard described previously [22], all cases were separated into two groups: a low expression level group for scores 0 and 1, and a high expression level group for scores 2 and 3.…”
Section: Methodsmentioning
confidence: 99%
“…The process was applied as previously described [22]. For wound healing assay, 6-well plates were chosen for healing assay.…”
Section: Methodsmentioning
confidence: 99%
“…Evidences including the important role of CXCL12/CXCR4 in tumor invasion and metastasis [1213] and its strong correlation with the poor prognosis in patients with esophageal cancer [1214] have been reported in literature. Therefore, in order to clarify the role of CXCL12/CXCR4 in the invasion and metastasis of ECSCs, we added a CXCR4 inhibitor AMD-070 to ECSCs, and observed its effect on ECSCs’ ability to invade and metastasize after incubation for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, p75NTR was introduced as a marker to identify esophageal cancerous cells with self-renewal and enhanced drug resistance [76]. Further studies characterized esophageal CSCs and proposed CD44 [77][78][79][80][81], CD133, CXCR4 [82], CD90 [83], and CD15 [78] as markers for esophageal stemlike cancer cells. ALDH1 activity has also been reported as a CSC marker in ESCC and esophageal adenocarcinoma (EAC), because ALDH1 + cells were highly proliferative and chemoresistant [84,85].…”
Section: Esophagusmentioning
confidence: 99%
“…Furthermore, the expression of OCT4 and SOX2 was significantly associated with higher histological grade and poorer survival of ESCC [93,94]. In addition, expression of CD133 [82] and CD44 [79,95,96], specifically CD44v6 [97,98], was associated with clinicopathological features of ESCC and EAC, although a number of studies reported contradictive results [99][100][101]. In addition, BMI1 overexpression was correlated to advanced pathological stage and lymph node metastasis in ESCC and EAC [102,103].…”
Section: Esophagusmentioning
confidence: 99%